Pengaruh masukan panas terhadap struktur mikro dan sifat mekanik sambungan pipa 5L X65 dengan proses pengelasan kombinasi STT SMAW - Muhamad Iqbal Farhani; M Thoriq Wahyudi; Mochammad Karim Al Amin (Politeknik Negeri Lhokseumawe, 2020)
Welding with the STT (Surface Tension Transfer) process is the latest innovation from the GTAW (Gas Tungsten Arc Welding) welding process, where STT is commonly used in the open root while the research carried out is the layer at the root and hot pass because it was chosen for the welding process with low heat input. . The research objective was to determine the effect of heat input or heat input of combination welding STT compared to GTAW on macro macro structure and mechanical properties of 5L X65 pipe welding joints. The results of this study compare the STT welding process with GTAW. Testing of the two processes will be assessed from the results of their mechanical properties through tensile and hardness, micro-macro structure and SEM. From the microstructure test and SEM, there is a not too significant effect on the differences in grain shape and content of ferrite acicular and ferrite widmanstatten, especially in the weldmetal area and grain changes in the HAZ area. From the hardness test, the comparison of the results of STT-SMAW, the hardness value is higher but not too significant than the GTAW-SMAW results due to the influence of heat input. The results from the tensile obtained that the STT-SMAW value has higher tensile strength and yield but not too significant compared to GTAW-SMAW, and all welding results still have values that fall into the standard range